SDK Arastamar Bone: Membangun Harapan di Tengah Keterbatasan - Nur Lestari; Yuni Hosiana Tobe (Jurnal Pengabdian Masyarakat, 2025)
Education in remote regions faces complex obstacles such as poor infrastructure, limited teachers, and transportation difficulties. Arastamar Christian Elementary School (SDK Arastamar Bone), founded in 2016 in Fat Village, Nunkolo District, Timor Tengah Selatan, East Nusa Tenggara, reflects the community’s determination to uphold children’s right to education despite isolation and constraints. This study describes the school’s efforts to deliver quality learning, strategies for sustainability, teaching innovations, and the support from parents, the community, and local authorities. Using a qualitative descriptive case study, data were obtained through interviews with teachers, parents, the principal, and education officials. Findings show that SDK Arastamar Bone symbolizes perseverance and hope. Teachers remain committed even with minimal salaries, while parents and villagers contribute voluntarily through labor, donations, and active participation. The foundation and government also provide vital support, ensuring continuity of educational activities. Despite enduring challenges such as limited facilities, staff shortages, and local skepticism, the school continues to thrive. The experience of SDK Arastamar Bone highlights that true educational success lies not only in material resources but also in collaboration, faith, and shared vision to nurture future generations in Indonesia’s remote communities.